2022
DOI: 10.1021/acs.biomac.2c01319
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Protein Stabilization with Zwitterionic Polypeptide–Cucurbit[7]uril Conjugates

Abstract: Protein aggregation is an obstacle for the development of new biopharmaceuticals, presenting challenges in shipping and storage of vital therapies. Though a variety of materials and methods have been explored, the need remains for a simple material that is biodegradable, nontoxic, and highly efficient at stabilizing protein therapeutics. In this work, we investigated zwitterionic polypeptides prepared using a rapid and scalable polymerization technique and conjugated to a supramolecular macrocycle host, cucurb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
2
5
0
Order By: Relevance
“…In contrast, compared to linear MS-70, the degraded pap-MS-70 exhibits a reduction in the degree of aggregation in the aqueous solution but maintains weak UCST-type behaviors. Owing to the impact of abundant charges from side chains belonging to the SBMA units, the degradation of the PMet backbone by papain is incomplete . This conclusion is also supported by SEC traces in Figure S16 and 1 H NMR spectra in Figure S17.…”
Section: Results and Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In contrast, compared to linear MS-70, the degraded pap-MS-70 exhibits a reduction in the degree of aggregation in the aqueous solution but maintains weak UCST-type behaviors. Owing to the impact of abundant charges from side chains belonging to the SBMA units, the degradation of the PMet backbone by papain is incomplete . This conclusion is also supported by SEC traces in Figure S16 and 1 H NMR spectra in Figure S17.…”
Section: Results and Discussionsupporting
confidence: 55%
“…Owing to the impact of abundant charges from side chains belonging to the SBMA units, the degradation of the PMet backbone by papain is incomplete. 45 This conclusion is also supported by SEC traces in Figure S16 and 1 H NMR spectra in Figure S17. The molecular weight distribution of pap-MS-70 becomes wider than that of MS-70, and the elution time is an intermediate between bottlebrush MS-70 and linear PSBMA-70.…”
Section: Thermal Responsiveness Of Ms-m Solutions In Watersupporting
confidence: 61%
See 1 more Smart Citation
“…This dictates the need for studying a noncovalent approach with other promising stealth alternatives (Hoang Thi et al, 2020), such as polyoxazolines (Bludau et al, 2017; de la Rosa, 2014) and zwitterionic systems (Blackman et al, 2019; Qu et al, 2022). In fact, a recent publication already describes the attachment of zwitterionic polypeptide structures based on the naturally occurring amino acid methionine to the protein via cucurbit[7]uril conjugation (Clauss et al, 2023). Overall, given the rapid emergence of versatile noncovalent methodologies and their evolving roles in the field of drug delivery and biomaterials (Webber, Appel, Meijer, & Langer, 2016; Webber & Langer, 2017), it is reasonable to expect significant advances in the development of noncovalently enabled stealth technologies in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PEGylation, Kramer et al have illustrated an alternative avenue for achieving supramolecular stabilization of insulins using the conjugates of CB [7] and zwitterionic polypeptides (CB [7]−PMets, Figure 4). 31 Their investigation revealed that the degree of polymerization of the zwitterionic polypeptides played a pivotal role in influencing the inhibitory efficacy, with optimal outcomes achieved when the degree of polymerization exceeded 80-mer. Moreover, the zwitterionic polypeptides were nontoxic to human cells and could be degraded by nonspecific native protease.…”
Section: Site-selective Modification Of Peptides/proteins By Macrocyclesmentioning
confidence: 99%